2011
DOI: 10.1100/2011/486259
|View full text |Cite
|
Sign up to set email alerts
|

Viable Extreme Preterm Birth and Some Neonatal Outcomes in Double Cerclage versus Traditional Cerclage: A Randomized Clinical Trial

Abstract: The pregnant women at higher risk of preterm labor, referred to the perinatal clinic of Kosar University Hospital in Urmia district of Iran, were enrolled into a parallel randomized clinical trial. In the investigational arm of the clinical trial, a double cervical cerclage procedure was performed addition to McDonald cerclage. In the control group however, only McDonald cerclage was performed. Extreme preterm labor (GA < 33 weeks) was the primary endpoint of this clinical trial. Age, gestational age at cercla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…One, comprising of 33 women, found that the preterm birth rate less than 34 weeks was comparable between the two groups (10.5% versus 35.7%; P = 0.106) 70 . The second found there was no significant difference in prolongation of the pregnancy between single and double cerclage, however, preterm birth less than 33 weeks was not experienced by any of the women in the double cerclage group and five in the single cerclage group 71 . The total number of participants in both studies was very small so limited conclusions can be drawn.…”
Section: Operative Issuesmentioning
confidence: 95%
See 1 more Smart Citation
“…One, comprising of 33 women, found that the preterm birth rate less than 34 weeks was comparable between the two groups (10.5% versus 35.7%; P = 0.106) 70 . The second found there was no significant difference in prolongation of the pregnancy between single and double cerclage, however, preterm birth less than 33 weeks was not experienced by any of the women in the double cerclage group and five in the single cerclage group 71 . The total number of participants in both studies was very small so limited conclusions can be drawn.…”
Section: Operative Issuesmentioning
confidence: 95%
“…70 The second found there was no significant difference in prolongation of the pregnancy between single and double cerclage, however, preterm birth less than 33 weeks was not experienced by any of the women in the double cerclage group and five in the single cerclage group. 71 The total number of participants in both studies was very small so limited conclusions can be drawn. Further RCTs are warranted to assess whether double cerclage may be superior to single.…”
Section: Evidence Level 2+mentioning
confidence: 98%
“…They also concluded that the double cervical cerclage procedure may be effective in preventing preterm delivery and improving perinatal outcome in cervical incompetence. In another study, Broumand et al . demonstrated that the gestational age was a period of 1.2 weeks longer for those patients who underwent the double cerclage method as compared to the single cerclage method, although the difference was not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 95%
“…However, some studies have reported that the effectiveness of the single cerclage method would be limited in this group of patients. They have recommended different procedures, including the placement of a cerclage suture close to the internal os and the placing of a double cervical cerclage in both the upper and lower portions of the cervix …”
Section: Introductionmentioning
confidence: 99%